1960
DOI: 10.1161/01.cir.21.1.63
|View full text |Cite
|
Sign up to set email alerts
|

The Vectorcardiogram and Electrocardiogram in Persistent Common Atrioventricular Canal

Abstract: The electrocardiogram and vectoreardiogram are of great aid in differentiating atrial septal defect of the secundum type from the ostium-primum type. In the latter condition there is left axis deviation in the scalar electrocardiogram and superior orientation of the QRS vector in the sagittal and frontal planes. There are relatively few congenital lesions that lead to the same degree of axis deviation and superior orientation of the QRS vector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

1960
1960
1981
1981

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The characteristic features of endocardial cushion defects (Toscano-Barbosa, Brandenburg, and Burchell, 1956;Beregovich et al, 1960;Burchell, DuShane, and Brandenburg, 1960), namely left axis deviation (frontal plane axis between 0 and -90°) with partial right bundle-branch block and a deep or slurred S wave in "posterior" leads II, III, and VF, were present in most cases. A long P-R interval (more than 0-2 sec.…”
Section: Investigationsmentioning
confidence: 97%
“…The characteristic features of endocardial cushion defects (Toscano-Barbosa, Brandenburg, and Burchell, 1956;Beregovich et al, 1960;Burchell, DuShane, and Brandenburg, 1960), namely left axis deviation (frontal plane axis between 0 and -90°) with partial right bundle-branch block and a deep or slurred S wave in "posterior" leads II, III, and VF, were present in most cases. A long P-R interval (more than 0-2 sec.…”
Section: Investigationsmentioning
confidence: 97%
“…The findings of Toscano-Barbosa have been confirmed by 'a few other authors (2,3,5,9,15). I n several of these publications, however, there has been inadequate checking of the diagnosis by autopsy or operation, even when all cases are registered as "proved".…”
mentioning
confidence: 81%
“…Burchell et al [12] found rare exceptions in the complete atrio-ventricular (A V) [8,13,14] found it in all cases. In almost all patients the QRS duration is prolonged [10].…”
Section: Endocardial Cushion Defectsmentioning
confidence: 99%